Effects of gibberellins on important agronomic traits of horticultural plants - Zhang, Xiaojia; Zhao, Baolin; Sun, Yibo; Feng, Yulong (Frontiers in Plant Science, 2022)
Horticultural plants such as vegetables, fruiters and ornamental plants are crucial to human daily life and socioeconomic development. Gibberellins (GAs), a class of diterpenoid compounds, control numerous developmental processes of plants. Many scientists have studied the roles of GAs in regulating growth and development of horticultural plants, and significant progress has been made. These findings have significant implications for promoting the quality and quantity of the products of horticultural plants. Here we reviewed the recent progress of the roles of GAs (biosynthesis and signaling) in regulating plant stature, axillary meristem outgrowth, compound leaf, flowering time, parthenocarpy and other agronomic traits of horticultural plants. We also discussed the effects of GAs on cell fate and GA movement in plant organs. These findings will provide a solid foundation for further modified the quality and quantity of horticultural plants products.